Association of Prescription With Body Composition and Patient Outcomes in Incident Peritoneal Dialysis Patients - Verger, Christian; Ronco, Claudio; Van Biesen, Wim; Heaf, James; Vrtovsnik, François; Vera Rivera, Manel; Puide, Ilze; Azar, Raymond; Gauly, Adelheid; Atiye, Saynab; De los Ríos, Tatiana (Frontiers in Medicine, 2021)
Objective: The nutritional status of patients on peritoneal dialysis (PD) is influenced by patient- and disease-related factors and lifestyle. This analysis evaluated the association of PD prescription with body composition and patient outcomes in the prospective incident Initiative for Patient Outcomes in Dialysis–Peritoneal Dialysis (IPOD-PD) patient cohort. Design and Methods: In this observational, international cohort study with longitudinal follow-up of 1,054 incident PD patients, the association of PD prescription with body composition was analyzed by using the linear mixed models, and the association of body composition with death and change to hemodialysis (HD) by means of a competing risk analysis combined with a spline analysis. Body composition was regularly assessed with the body composition monitor, a device applying bioimpedance spectroscopy. Results: Age, time on PD, and the use of hypertonic and polyglucose solutions were significantly associated with a decrease in lean tissue index (LTI) and an increase in fat tissue index (FTI) over time. Competing risk analysis revealed a U-shaped association of body mass index (BMI) with the subdistributional hazard ratio (HR) for risk of death. High LTI was associated with a lower subdistributional HR, whereas low LTI was associated with an increased subdistributional HR when compared with the median LTI as a reference. High FTI was associated with a higher subdistributional HR when compared with the median as a reference. Subdistributional HR for risk of change to HD was not associated with any of the body composition parameters. The use of polyglucose or hypertonic PD solutions was predictive of an increased probability of change to HD, and the use of biocompatible solutions was predictive of a decreased probability of change to HD. Conclusion: Body composition is associated with non-modifiable patient-specific and modifiable treatment-related factors. The association between lean tissue and fat tissue mass and death and change to HD in patients on PD suggests developing interventions and patient counseling to improve nutritional markers and, ultimately, patient outcomes. Study Registration: The study has been registered at Clinicaltrials.gov (NCT01285726).